2008
DOI: 10.1021/jp711246b
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Configurations and Reactions of Boric Acid on a TiO2 Anatase (101) Surface

Abstract: This study investigates the adsorption and reactions of the monomer and dimer of B(OH)3 on a TiO2 anatase (101) surface by first-principles calculations based on the density functional theory and pseudopotential method. On the clean surface, the most stable adsorption structure for B(OH)3 is a molecular monodentate configuration with one hydrogen bonded to a neighboring surface bridging oxygen. The adsorbed B(OH)3 molecule can dissociate into the bidentate adsorption configuration, Ti−OB(OH)O−Ti(a), in which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 48 publications
20
46
0
Order By: Relevance
“…As summarized in Table 1, the adsorption energy with hydrogen attaching to a neighboring oxygen site decreases in the range of 0.2-11.9 kcal/mol. These results indicate that the hydrogen coadsorption may destabilize the SiH x adsorption on the TiO 2 anatase (101) surface, unlike the enhancement effects of H-coadsorption on the binding of OH, [57,58] HS, [19] NO 3 , [21] and HOBO 2 [16] species with titania. …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As summarized in Table 1, the adsorption energy with hydrogen attaching to a neighboring oxygen site decreases in the range of 0.2-11.9 kcal/mol. These results indicate that the hydrogen coadsorption may destabilize the SiH x adsorption on the TiO 2 anatase (101) surface, unlike the enhancement effects of H-coadsorption on the binding of OH, [57,58] HS, [19] NO 3 , [21] and HOBO 2 [16] species with titania. …”
Section: Resultsmentioning
confidence: 93%
“…To improve the heterogeneous interface between a QD and TiO 2 and achieve higher efficiencies, there have been attempts to search for a variety of linkers (e.g., H 3 BO 3 , [16,17] BCl x , [18] H 2 S, [19] H 2 O 2 , [20] and HNO 3 , [21] ). An alternative material, the well-known silicon has been studied extensively for the solar cell applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The luminescence intensity is strongly related with the radiative recombination of photogenerated electrons and holes, so the higher the intensity of PL, the greater the likelihood of occurrence of electron-hole recombination processes [44]. For both materials, the registered PL spectra are characterized by a broad band in the range of 480-600 nm with a maximum at 530 nm that is attributed to activity of surface states [45]. The doped titania nanotubes exhibit lower intensity of photoluminescence than pure TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…A density functional tight binding study of acetic acid on TiO2 on anatase (101), rutile (110), and brookite (001) identified a bidentate configuration(4) on all politypes. First-principles calculations using DFT+U show a molecular monodentate geometry of formic acid on TiO2,(5, 6) while standard GGA calculations (7,8) and tight-binding(9) predicted a bidentate geometry.…”
Section: Introduction Asmentioning
confidence: 99%